Experimental study of capacity and electrode structure of six cell dynamic lead acid battery - Kurriawan Budi Pranata; Yuni Triasari; Nur Khairati; Istiroyah Istiroyah; Mauludi Ariesto Pamungkas; Muhammad Ghufron (Universitas Ahmad Dahlan, 2021)
The six cells of the dynamic lead acid battery (DLAB) series have been made to resemble the accumulator with sulfuric acid single electrolyte. The tank was filled with 1200 mL of 30% sulfuric acid and circulated through each unit cell by a minipump during charge-discharge process. Experiments were carried out by providing a charging current of 2A, while the discharge current was varied at 0.5 A, 0.6 A, 0.7 A, 0.8 A for 10 continuous cycle to obtain the battery with the best characteristics. The experimental results show that all batteries have a working voltage of 10.8-14.4 volt. The discharging current is inversely proportional to the discharging duration. The resulting capacity has an efficiency ranging from 80.1-81.1%. DLAB with 0.5 A discharging current shows the best performance based on the length of duration and the average capacity with value of 109.61 h and 6168 mAh while for the ideal performance stability is obtained by DLAB with 0.7 A discharging current. The electrochemical reaction produces angelsite and plattnerite phases on the positive electrode. Meanwhile, angelsite and lead phases are formed on the negative electrode.